Controlled release of metformin-loaded SA/PEG scaffolds produced by 3d-printing technology - Harmanci, Sena; Cesur, Sumeyye; Gunduz, Oguzhan; Ustundag, Cem Buelent (YILDIZ TECHNICAL UNIV, 2023)
Type 2 diabetes mellitus (T2DM) is a long-term metabolic disease that is commonly characterized by insulin deficiency or resistance, and prevalence has been increasing gradually all over the world. The aim of this study is to produce Metformin-loaded 3D printed scaffolds for an alter-native drug delivery application in the treatment of Type 2 DM with two different biopolymers. Sodium Alginate (SA)/Polyethylene glycol (PEG) scaffolds loaded with varying concentrations of Metformin (0.5 and 2 wt.%) were prepared by adding 9 wt.% of SA to 3 wt.% of PEG. The physical analyses of the solutions were examined after the production process, and as a result, no significant changes were observed in the viscosity, density, and surface tension of the solutions with the addition of Metformin. Morphological (SEM), molecular interaction (FTIR), thermal analysis (DSC), tensile strength analyses were done. SEM images and histograms showed that the desired pore structure was obtained in the scaffolds produced by the 3D printing method, and the average pore sizes were 236.14 +/- 18.999, 255.28 +/- 14.168, and 318.83 +/- 13.038 mu m for SA/ PEG, 0.5% and 2% Metformin-loaded scaffolds, respectively. A drug release test was performed by UV spectroscopy. Metformin from both 0.5% and 2% scaffolds showed a burst release in 30 minutes because of the high solubility of SA and PEG in water. More than 97% of the drug was released from both scaffolds. However, they displayed sustained release up to 24 hours. Therefore, Metformin-loaded 3D-printed scaffolds have promising potential for the treatment of T2DM as they are an alternative to the oral administration of the drug.
Keywords: 3D Printing; Drug Release; Metformin; Diabetes Mellitus; DRUG-DELIVERY; PORE-SIZE; POLY(ETHYLENE GLYCOL); 3D; BIOMATERIALS; Engineering